2019
DOI: 10.1123/jsr.2018-0092
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Strength Deficits in a Cohort of College Athletes With Chronic Ankle Instability

Abstract: Collegiate athletes who present with mechanical laxity on a previously injured ankle exhibit PF and EV strength deficits between ankles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
6
0
2
Order By: Relevance
“…Comparable to our data, several studies have provided evidence that concentric pronation and supination strength are impaired in CAI [10][11][12]. The novel finding in this study was that the joint angle in which the maximum pronation strength can be produced is significantly different between the two ankles (MAI 14°vs.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Comparable to our data, several studies have provided evidence that concentric pronation and supination strength are impaired in CAI [10][11][12]. The novel finding in this study was that the joint angle in which the maximum pronation strength can be produced is significantly different between the two ankles (MAI 14°vs.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, a recent systematic review found that impairments of peroneal reaction time and pronation strength strongly contribute to perceived ankle instability in a chronic population [10]. Also, strength deficits resulting from ankle injuries have been described especially in plantarflexion and pronation strength, while dorsiflexion and supination strength seems to remain rather unaffected [11,12]. It is thought that spinal and cortical pathways may lead to an inhibition of neuromuscular activity and thus contribute to these persisting deficiencies in CAI patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, participants with CAI had significantly reduced plantarflexion and dorsiflexion ROM, inversion and eversion strength, and muscular endurance as assessed in two different single leg heel raise tests. These findings are consistent with previous research, whereby deficits in a variety of measures of ankle function have been observed in individuals with CAI ( Gribble et al, 2014 ; Silva et al, 2013 ; Wisthoff et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…6,7 An association with functional instability scores for CAI has also been reported. 8 Structural changes at the ligament and bone level due to childhood LAS may be associated with progression to CAI secondary to LAS.…”
Section: Introductionmentioning
confidence: 99%